Islam and Asia Pacific Muslims: the implications of spirituality for social work practice. - Hall, RonaldE.; Livingston, JonathanN.; Brown, CamilleJ.; Mohabir, JessicaA. (Journal of Social Work Practice, 2011)
Among Asia Pacific Muslim populations, spirituality is fundamental. The implications of spirituality for social work intervention with Muslim populations include the need for social work practitioners to acknowledge, and when appropriate, apply values, belief systems, and other Islamic specific spiritual criteria. The dampening effects of traditional social work practice without Islamic spiritual resources will lessen the potential of social work intervention. Effective and efficient social work practice, involving Asia Pacific Muslim clientele, must necessarily incorporate knowledge of Islam. The ability of social workers to accurately perceive, conceptualize, and interact therapeutically with Asia Pacific Muslim clients is a necessity in a rapidly changing and complex world.